Cigarette smoking and cardiovascular disease incidence and all-cause mortality: the modifying role of diet quality - Mostafa Norouzzadeh; Farshad Teymoori; Hossein Farhadnejad; Nazanin Moslehi; Parvin Mirmiran; Seyedeh Tayebeh Rahideh; Fereidoun Azizi (BMC, 2024)
Abstract Background This study examines the potential long-term joint association between smoking and diet quality as modifiable risk factors concerning cardiovascular diseases (CVDs) incidence and all-cause mortality among current and former smokers. Methods The study followed 955 smokers from the third and fourth examinations of the Tehran Lipid and Glucose Study to March 2018. Dietary data was collected using a food frequency questionnaire. Three diet quality indices (DQIs) were computed at baseline: DQI-international (DQI-I), DQI-revised (DQI-R), and Mediterranean-DQI (Med-DQI). Cox proportional hazards regression models were used to determine the HR (95% CI) of the joint association between smoking and diet quality among heavy and light smokers, based on the number of cigarettes per day and pack-years, as well as between current and former smokers based on smoking habits. Results Over a follow-up period of almost eight years, 94 cases of CVDs (9.80%) and 40 cases of mortality (4.20%) were documented. The lower diet quality based on the Med-DQI was associated with a higher risk of mortality among current smokers (HR:3.45; 95%CI:1.12, 10.57). Light smokers with good diet quality, compared to heavy smokers with poor diet quality, had a lower risk of CVDs incident (HR:0.35; 95%CI: 0.15, 0.83) and all-cause mortality (HR:0.20; 95%CI:0.05, 0.77). Current smokers with good DQI had a lower risk of mortality compared to current smokers with poor DQI (HR:0.26; 95%CI:0.08, 0.80). However, this lower risk was more significant in former smokers with good DQI (HR:0.10; 95%CI:0.02, 0.45). Conclusions Light and former smokers had a lower risk of developing CVDs and experiencing mortality. However, when coupled with a high-quality diet, this protective effect is even more pronounced.